ANALISIS PERILAKU SISWA DALAM PROSES BELAJAR YANG MENGALAMI KELUARGA BROKEN HOME DI SMPN - Suci Rahmawati; Rustiyarso Rustiyarso; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of this thesis is "The Analysis of Student's Behavior Who Experienced a Broken Home Family in the Learning Process of Social Science Subject class VIIIGin SMPN 9 Pontianak". The general problem of this thesis was the behavior of student's who experienced a broken home family in SMPN9 Pontianak. The purpose of this research was to determine the behavior of students who experienced a broken home family in term of student's learning habit, student's attention in learning, and the tendency of student's learning attitude in SMPN 9 Pontianak. The approach used in this research was the qualitative approach with the descriptive method. The techniques of data collection used in this research were observation, interview and documentation. Tools of data collection used in this research were observation guides, interview guidesand notebook with archives. Techniques of data analysis used in this research were data reduction, data presentation and conclusions drawing. The analysis of this study was presented descriptively based on 5 informants consisted of one social science subject teacher initially Mrs. NB and four students who experienced a broken home family in class VIII G initially FP, N, AP and B. The result of this research indicated the study habit of students who have a broken home family was commonly late coming to school before the class began, but the students who experienced a broken home family trained to learn until they comprehended the lesson. Students who experienced a broken home family sometimes distracted their sight in the middle of the learning process of social science subject, students who experienced a broken home family were not interested in reading and writing conclusions of the lesson or underlined the important point of the lesson in the school especially during the learning process of social science subject.Keywords: Student's Learning Behavior, A Broken Home Family